2002
DOI: 10.1046/j.1460-9568.2002.02001.x
|View full text |Cite
|
Sign up to set email alerts
|

Creatine kinase B‐driven energy transfer in the brain is important for habituation and spatial learning behaviour, mossy fibre field size and determination of seizure susceptibility

Abstract: Creatine kinases are important in maintaining cellular-energy homeostasis, and neuroprotective effects have been attributed to the administration of creatine and creatine-like compounds. Herein we examine whether ablation of the cytosolic brain-type creatine kinase (B-CK) in mice has detrimental effects on brain development, physiological integrity or task performance. Mice deficient in B-CK (B-CK-/-) showed no gross abnormalities in brain anatomy or mitochondrial ultrastructure, but had a larger intra- and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(117 citation statements)
references
References 75 publications
(97 reference statements)
10
105
1
1
Order By: Relevance
“…This suggests that creatine supplementation is acting to smooth fluctuations in the blood oxygen level dependent response curve which results from brain activation (Gjedde et al 1999;Madsen et al 1999), possibly by altering rates of ATP synthesis in the mitochondrion through the mitochondrial creatine kinase-adenine nucleotide translocase-porin complex (Wallimann et al 1992;Saks et al 2000). Most recently, deletion of cytosolic brain-type creatine kinase in mice was shown to result in slower learning of a spatial task and diminished open-field habituation as well as increased intra-and infra-pyramidal hippocampal mossy fibre area suggesting that the creatine-creatine kinase network is also involved in brain plasticity in addition to metabolism ( Jost et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that creatine supplementation is acting to smooth fluctuations in the blood oxygen level dependent response curve which results from brain activation (Gjedde et al 1999;Madsen et al 1999), possibly by altering rates of ATP synthesis in the mitochondrion through the mitochondrial creatine kinase-adenine nucleotide translocase-porin complex (Wallimann et al 1992;Saks et al 2000). Most recently, deletion of cytosolic brain-type creatine kinase in mice was shown to result in slower learning of a spatial task and diminished open-field habituation as well as increased intra-and infra-pyramidal hippocampal mossy fibre area suggesting that the creatine-creatine kinase network is also involved in brain plasticity in addition to metabolism ( Jost et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The causes of decreased levels of cytosolic brain CK isoform (BB-CK) in postmortem brain in mental pathology are subject of discussions 15 . As it was recently demonstrated, BB-CK energy transfer in the brain is important for habituation and spatial learning behaviour 16 . Dynamic study of 31 P MR spectroscopy revealed strong reduction of PCr New magnetic resonance spectroscopy biomarker for monitoring neurodegenerative diseases: animal models =>ATP phosphorus flux in mice with ablation of cytosolic BB-CK, while ATP and PCr levels were unaffected in these mice 16 .…”
Section: Adult Ratsmentioning
confidence: 93%
“…As it was recently demonstrated, BB-CK energy transfer in the brain is important for habituation and spatial learning behaviour 16 . Dynamic study of 31 P MR spectroscopy revealed strong reduction of PCr New magnetic resonance spectroscopy biomarker for monitoring neurodegenerative diseases: animal models =>ATP phosphorus flux in mice with ablation of cytosolic BB-CK, while ATP and PCr levels were unaffected in these mice 16 . Thus, the rate constant of CK, k for measured in the brain reflects changes of BB-CK activity 8,9,16 .…”
Section: Adult Ratsmentioning
confidence: 93%
“…Located in the cytoplasm of glial cells 38 and GABAergic interneurons, 39 CKB reversibly catalyses the transfer of phosphate between ATP and various phosphogens such as creatine phosphate, 40 important in the brain for habituation, spatial learning and behaviour. 41 Cells with high CKB expression are known to be resistant to neurological insults, such as glucose and oxygen deprivation 39 and as such the increased CKB expression in the ACC gray matter may protect cells from oxidative damage observed in the disease state. However, activity of CKB is thought to be reduced in the frontal cortex, anterior and posterior cingulate, hippocampus and cerebellum in schizophrenia.…”
Section: Metabolismmentioning
confidence: 99%